"All Voices Matter": Perspectives on Bridging the Campus-to-Community Gap - Keisha D. Ivey; Kaleb Murry; Deanna Dragan; Marcus Campbell; Jacqueline Maye; Christopher Spencer (The University of Alabama, 2022)
Project Sharing Opinions and Advice about Research in the Deep South (SOAR) aims to increase the involvement of community members to enhance the importance, relevance, and cultural appropriateness of disease research and interventions offered in the Deep South. SOAR recruits and trains community partners to include them in conversations about how best to identify and address mental and physical health disparities. Additionally, SOAR underscores the importance of addressing issues faced by ethnically diverse and underserved community members.